Hand in hand : Aboriginal, Torres Strait Islander, Maori, Niuean and Fijian artists from Australia and beyond - Fraser, Jenny; Kihara, Shigeyuki; Boomalli Aboriginal Artists Cooperative; Performance Space CarriageWorks (Leichhardt, N.S.W. : Boomalli Aboriginal Artists Cooperative, 2008)
Australian Indigenous artists featured include: Arone Raymond Meeks, Adrian Wills, Darrell Sibosado, Tracey Moffatt, Jenny Fraser, Dianne Jones, Jeffrey Samuels, Gary Lee, Rea, Clinton Nain and includes brief biographies of each artist; includes two poems by Wendy Riley.
"An exhibition at Boomalli and Performance Space to celebrate Mardi Gras, 2008".
Catalogue of an exhibition held at Boomalli Aboriginal Artists Cooperative, Leichhardt, and Performance Space @ CarriageWorks, Sydney, 2008.
Keywords: Art, Aboriginal Australian -- Exhibitions; Gay artists -- Australia -- Exhibitions; Homosexuality and art -- Exhibitions; Art - Artists; Homosexuality; Art - Exhibitions